2022
DOI: 10.1016/j.ijintrel.2021.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Are we in this together? Changes in anti-immigrant sentiments during the COVID-19 pandemic

Abstract: The COVID-19 pandemic is posing a threat to people all across the globe. According to traditional literature, threat perceptions induce anti-immigrant sentiments, as ingroup identity and self-interest are strengthened at the expense of the outgroup. In this study, we investigate whether the COVID-19 pandemic indeed increases anti-immigrant sentiments, or that this type of threat elicits other or no group related responses. We also look at whether such responses are expressed more strongly among specific subgro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…Less is known about how situational factors could be associated with the relationship between well-being and ATM or preferences for asylum and refugee policies. Previous studies have shown that large-scale crises eliciting strong negative feelings, such as pandemics or economic cycles, may be associated with less favourable ATM and disturb the support for asylum and refugee policies (Adam-Troian & Bagci, 2021;Andrighetto et al, 2016;Esses & Hamilton, 2021;Muis & Reeskens, 2022). This is in line with realistic group conflict theory indicating that when resources -e.g.…”
Section: Negative Shifts In Attitudes Towards Migrantssupporting
confidence: 79%
See 2 more Smart Citations
“…Less is known about how situational factors could be associated with the relationship between well-being and ATM or preferences for asylum and refugee policies. Previous studies have shown that large-scale crises eliciting strong negative feelings, such as pandemics or economic cycles, may be associated with less favourable ATM and disturb the support for asylum and refugee policies (Adam-Troian & Bagci, 2021;Andrighetto et al, 2016;Esses & Hamilton, 2021;Muis & Reeskens, 2022). This is in line with realistic group conflict theory indicating that when resources -e.g.…”
Section: Negative Shifts In Attitudes Towards Migrantssupporting
confidence: 79%
“…Importantly, the results provide optimistic information that the effect of emotions upon attitudes could spill over beyond Ukrainian refugees. In other words, the newly emerged sense of shared fate may also include other ethnically or culturally more diverse groups of people in need (Muis & Reeskens, 2022). The fact that natives may perceive themselves to be equally threatened could, thus, reduce negative outgroup affect (Adam-Troian & Bagci, 2021;Andrighetto et al, 2016).…”
Section: Atm and Policy Preferences Born Of Sufferingmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a three-wave panel study starting in February 2020 in Poland found that people became more authoritarian and prejudiced towards sexual dissenters (Golect de Zavala et al, 2021), suggestive of a cultural conservative shift in that country. However, a two-wave panel study in the Netherlands starting in 2017 found that people became more supportive of gender equality and less supportive of immigrant prejudice (Muis & Reeskens, 2022;Reeskens et al 2021), contrary to a cultural conservative shift pattern.…”
Section: Constraints On Generalizabilitymentioning
confidence: 95%
“…Recent research argues that there is no clear trend of increased antipathy toward immigration as a pandemic threat to health is considered a common threat and natives have adopted a prosocial attitude toward resident immigrants on the basis of a conception of "we are all in the same boat". This is indicative of increasingly identifying, rather than avoiding or detesting these outgroups in response to pathogen threats [62][63][64]. Despite evidence of the favorable response, there is still an issue around whether a higher threshold for immigrants approaching the border will be perceived as acceptable by the public.…”
Section: Plos Onementioning
confidence: 99%